A qualitative study of the crime-control potency of traditional justice system in Oshogbo - Ayodele, Johnson Oluwole (The British journal of criminology, 2018)
This article examines the implications of the traditional justice system for crime control in Oshogbo. It used qualitative methods and a purposive sampling method to select 35 in-depth, 5 key informant interview participants and 3 major streets in Oshogbo, respectively. Data were content analyzed. The study found that the traditional and formal justices reduce customary and complex offenses with norms and laws, respectively. It concludes that a formal–traditional partnership will reduce criminality. It suggests the reorganization and co-optation of state and non-state systems under an institutional umbrella to reduce crime and improve public safety in Oshogbo.